2008
DOI: 10.1519/jsc.0b013e31815f30e7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early Phase Adaptations for Traditional Strength and Endurance, and Low Velocity Resistance Training Programs in College-Aged Women

Abstract: The purpose of this study was to investigate the effects of a six-week (16-17 training sessions) low velocity resistance training program (LV) on various performance measures as compared to a traditional strength (TS) and a traditional muscular endurance (TE) resistance training program. Thirty-four healthy adult females (21.1 +/- 2.7 y) were randomly divided into 4 groups: control (C), TS, TE, and LV. Workouts consisted of 3 exercises: leg press (LP), back squat (SQ), and knee extension (KE). Each subject was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 15 publications
1
52
1
1
Order By: Relevance
“…Subjects were informed that a pause for longer than 3 s after completion of a repetition or a significant loss of form would conclude the test. The total number of repetitions performed served as the measure for absolute muscular endurance [25]. The same load used in pre-testing was used for post-testing to evaluate improvements in absolute muscle endurance after 12 weeks of training.…”
Section: Muscular Strength and Endurancementioning
confidence: 99%
“…Subjects were informed that a pause for longer than 3 s after completion of a repetition or a significant loss of form would conclude the test. The total number of repetitions performed served as the measure for absolute muscular endurance [25]. The same load used in pre-testing was used for post-testing to evaluate improvements in absolute muscle endurance after 12 weeks of training.…”
Section: Muscular Strength and Endurancementioning
confidence: 99%
“…For the anterior and posterior upper arm, measurements were taken 60 % distal between the lateral epicondyle of the humerus and the acromion process of the scapula; for the vastus lateralis, measurements were taken 50 % between the lateral condyle of the femur and greater trochanter for the quadriceps femoris. Ultrasound has been validated as a good measurement of muscle volume in these muscles [20,21], and has been used in numerous studies to evaluate hypertrophic changes [19,[22][23][24][25].…”
Section: Muscle Thicknessmentioning
confidence: 99%
“…A purposely slow resistance exercise training session such as used in the present study requires lifting external loads between 25-50% 1 RM [10,12,13,20,24]. In cases where high power, strength, and speed is required, as in sports, athletes need to be able to produce high levels of muscle force and power, and high contraction velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Since traditional resistance exercise produces greater energy expenditure than purposely slow velocity resistance exercise, it may be a more beneficial protocol for body mass control [10]. In a different study, purposely slow velocity resistance exercise with untrained women has been shown to improve muscular strength and muscular endurance, but not to a greater extent than traditional strength training [20]. It has also been reported that slow velocity resistance training resulted in greater strength increases when compared to traditional velocity training, however, different methods of strength testing were used for each group, thus drawing into question the results [23].…”
Section: Introductionmentioning
confidence: 99%